Designing a Financial Statement Information Quality Model for Fraud Prevention in the Palangka Raya City Government - Dhina Sri Widyaningsih; Pratiwi Hamzah; Wahyu Febri Eka Susanti (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The increase in fraud incidents in local government has prompted the need for a financial reporting quality model that supports fraud prevention at the government level, particularly in the Palangka Raya City Government. This study designs a conceptual model that links Quality of Financial Reporting (QFR) with the effectiveness of fraud prevention, as well as identifying important mediator and moderator roles. The methods used are a literature review and desk study of academic literature, regulations, and local government financial reporting documents. The synthesis results confirm five main dimensions of QFR: relevance, reliability (faithful representation), comparability, timeliness, and understandability. The proposed model places the Government Internal Control System (SPIP)/internal audit as a mediator between QFR and fraud prevention, while fraud analytics, whistleblowing systems, and a culture of integrity act as moderators that strengthen this relationship. Practical recommendations include strengthening SPIP, integrating analytical technology for early detection, and reporting and whistleblower protection mechanisms to close opportunities for fraud. Implementation of this model is expected to strengthen regional financial governance and reduce the risk of fraud through the synergy of preventive, detection, and response measures.